Implementasi Akuntansi Salam Dalam Laporan Keuangan: Studi Kasus PT Bank Syariah Indonesia - Aprilia Safitri; Putri Diar Utami; Sri Widiastuti; Riski Rudianto; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Profit-sharing system in Islamic banks is one of the applications of Sharia since interest contradicts Islamic law. Islamic banks can engage in banking activities like non-Islamic banks as long as they do not contradict Sharia principles. Salam accounting is in the financial statements of PT Bak Syariah Indonesia and to ascertain the conformity of the accounting implementation with PSAK No. 59 and the Fatwa of DSN MUI. aimed at providing an overview of the object based on observable facts and providing an examination of the financial statement application comparison between the research item, PSAK No. 59, and the DSN MUI Fatwa. The findings indicate that PT Bak Syariah Indonesia employs Salam contracts with the following service items in order to execute Sharia accounting for Sharia service products: The application of Sharia accounting for Sharia service goods at PT Bak Syariah Indonesia, as well as Qardh: Haji Guarantee Fund, Export L/C, is in accordance with PSAK No. 59.